Various prosthodontic options for malpositioned implants in the anterior region: A narrative review - Archana K Sanketh; Shrutika; N. Kalavathy; Mitha Shetty; Roshan Kumar; V Anuradha (SRM Journal of Research in Dental Sciences)
Dental implants are now widely used in a wide range of clinical settings because of the growing research in the field of dental implantology. Dental implant placement is becoming more and more prevalent, which might lead to complications. One common issue is placing a dental implant improperly. The restorative dentist, laboratory technician, and the patient have an enormous challenge when it comes to prosthetically unfavorable implant rehabilitation. Aim: The purpose of this narrative review is to discuss classic prosthodontic challenges faced by clinicians for anterior implant restorations when the alterations/improvement of the surgical site is not an option and requests for rehabilitation of the existing situation. Methods: Researchers conducted a search of 13 studies using databases from the Cochrane Library, EBSCO, EMBASE, PubMed, and Web of Science. It gathered articles published from January 2000 to December 2023 with comprising terms such as “Angulated Abutment, Angulated Screw access, UCLA abutment, Cross-pin screw-retained implant prosthesis, Gingival ceramic collar.” Results: A total of 13 articles were collected and used to formulate this review. It describes different scenarios for correction of esthetic complications of malpositioned anterior implant region with a focus on prosthesis design and material selection. Other aspects such as advantages, disadvantages, and complications of different prosthetic options are also considered. Discussion: Even in cases where the implants are misaligned or malpositioned, labially located screw access of anterior implant restoration can be nonsurgically managed at the abutment level; material basis and prosthesis type (fixed or removable) may contribute to both esthetic and functional restorations. Conclusion: A thorough esthetic analysis of both hard and soft tissues, as well as precise treatment planning, may be required to achieve an optimal outcome during treatment. However, in certain cases, surgical corrections rather than prosthetic modifications would be required to improve results, which may pose a limitation.